2008
DOI: 10.2967/jnumed.107.046102
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Serotonin Transporter Ligand 123I-ADAM for SPECT Studies on Humans

Abstract: Imaging serotonin transporters in the living human brain is important in several fields, such as normal psychophysiology, mood disorders, eating disorders, and neurodegenerative disorders. The aim of this study was to compare different kinetic and semiquantitative methods for assessing serotonin transporters using 123 I-labeled 2-((2-((dimethylamino)methyl)phenyl)thio)-5-iodophenylamine (ADAM) in humans: an arterial plasma input model, simplified and Logan reference tissue models, and standardized uptake value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Nevertheless, it has been demonstrated for [ 123 I]ADAM in baboons, that a simple ratio method gave a strong correlation with the full kinetic model (R 2 =0.89); the reference tissue model was only minimally better (R 2 =0.94) (Acton et al 2001). Furthermore, Frokjaer et al (2004) evaluated [ 123 I]ADAM in human subjects, and concluded that the use of the cerebellum as the reference tissue seemed to be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated for [ 123 I]ADAM in baboons, that a simple ratio method gave a strong correlation with the full kinetic model (R 2 =0.89); the reference tissue model was only minimally better (R 2 =0.94) (Acton et al 2001). Furthermore, Frokjaer et al (2004) evaluated [ 123 I]ADAM in human subjects, and concluded that the use of the cerebellum as the reference tissue seemed to be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the need of accurate determination of plasma metabolites as well as of the free fraction of plasma unmetabolized parent radioligand, arterial sample measurements often appear to be less reproducible (Ichise et al, 2001). In a preliminary SPECT study Frokjaer et al (2004) demonstrated good correlation between full kinetic modelling and a simplified reference tissue model in humans.…”
Section: Discussionmentioning
confidence: 92%
“…A recent DATSCAN study has revealed moderately reduced abundance of dopamine transporters in striatum of never-treated patients with schizophrenia (Mateos et al 2007 ) , which seems somewhat at odds with the fi nding of increased effects of amphetamine, noted above. The [ (Frokjaer et al 2008 ) ; SPECT studies with this tracer have revealed increased serotonin transporters in the brainstem of subjects with borderline personality disorder (Koch et al 2007 ) , and have shown the occupancy at serotonin transporters in depressed patients under treatment with citalopram (Herold et al 2006 ) . SPECT tracers for serotonin receptors, as opposed to presynaptic serotonin transporters, are not yet widely available.…”
Section: The Radiation Physics Of Molecular Imagingmentioning
confidence: 99%